Fighting for "Justice for all" in an era of deepening exploitation and ecological crisis - Bradshaw, Elizabeth (Demystifying power, crime and social harm, 2023)
Reading Box today evokes a sense of familiarity: 40 years later, critical criminology is writing about the same problems with harsh criminal justice for the poor, impunity for harmful corporate crime, and mainstream criminology fixing a system that provides law and order to an unjust society. In honoring Box’s early framing of these issues, our chapter aims to connect his work to young people subjected to increasing exploitation, environmental destruction, and governments more intent on criminalizing youth than helping them. First, using insights from The Rich Get Richer and the Poor Get Prison, this chapter expands on Box’s analysis to explore ideological reasons for the continuation of injustice. Second, expanding on his comments about the oil industry, we discuss climate crimes by the fossil fuel industry and government - state-corporate crimes - that especially threaten youth with a dangerous and troubled future. Third, we examine dissent and protest by youth who are faced with the existential threat of climate change while governments sit idly by. In conclusion, we discuss how ideology prevents youth (and citizens generally) from effective challenges to social injustice. The challenge for the next 40 years is what we do about these injustices, which requires criminology supporting protests by those victimized by carbon criminals and economic exploitation.